Functional diversification of the chemical landscapes of yeast Sec14-like phosphatidylinositol transfer protein lipid-binding cavities - Tripathi, Ashutosh; Martinez, Elliott; Obaidullah, Ahmad J.; Lete, Marta G.; Lönnfors, Max; Khan, Danish; Soni, Krishnakant G.; Mousley, Carl J.; Kellogg, Glen E.; Bankaitis, Vytas A. (The Journal of biological chemistry, 2019)
Phosphatidylinositol-transfer proteins (PITPs) are key regulators of lipid signaling in eukaryotic cells. These proteins both potentiate the activities of phosphatidylinositol (PtdIns) 4-OH kinases and help channel production of specific pools of phosphatidylinositol 4-phosphate (PtdIns(4)P) dedicated to specific biological outcomes. In this manner, PITPs represent a major contributor to the mechanisms by which the biological outcomes of phosphoinositide are diversified. The two-ligand priming model proposes that the engine by which Sec14-like PITPs potentiate PtdIns kinase activities is a heterotypic lipid-exchange cycle where PtdIns is a common exchange substrate among the Sec14-like PITP family, but the second exchange ligand varies with the PITP. A major prediction of this model is that second-exchangeable ligand identity will vary from PITP to PITP. To address the heterogeneity in the second exchange ligand for Sec14-like PITPs, we used structural, computational, and biochemical approaches to probe the diversities of the lipid-binding cavity microenvironments of the yeast Sec14-like PITPs. The collective data report that yeast Sec14-like PITP lipid-binding pockets indeed define diverse chemical microenvironments that translate into differential ligand-binding specificities across this protein family.